Diseño de un pozo geonavegado usando sistemas rotativos direccionales híbridos (2016)
This article will show the design of a well to the K1 lateral navigation Training in the Oilfield Castilla Ecopetrol S.A. reducing drilling four days about the best studied well which was performed in 15.6 days at a savings of up to$ 320,000. Well design has been carried out in 5 steps, technology research, trajectory design, BHA design, technical discussion and economical discussion.